Control of an asymmetric alternate arm converter for HVDC - Soto Sanchez, Diego Enrique; Hernández, M.; Andrade Aguero, Ivan Eric; Peña, R. (My University, 2017)
The Modular Multilevel Converter (MMC) has become the choice topology for integration of renewable energy power plants into the grid, through submarine HVDC cables and HVDC lines. Nevertheless, the MMC requires significant large DC storage capacitors to mitigate for the large power pulsations that result from the single-phase like AC to DC conversion process that takes place in the arms. This work addresses a converter topology which uses modular multilevel arms only on the lower side of the MMC converter whereas the upper side uses only standard ON-OFF valves. This corresponds to a limit case of the Alternate Arm Converter (AAC) with no module on the upper side and no director switch on the lower side, i.e. an Asymmetrical ACC. Like the AAC, the Asymmetric AAC offers a significant reduction in DC energy storage requirements. In addition, the Asymmetric AAC offers a less restricted operation than the AAC, in terms of operating over a wide range of AC to DC voltage ratio, and the possibility of achieving both distortion-free AC current and ripple-free DC current. The principle of operation of the Asymmetric AAC is explained in detail and a suitable control strategy to demonstrate its operation is developed. Proposals are verified through simulation studies and experiments conducted on a low power prototype. Results confirm good operation of the proposed converter and control scheme.
Keywords: alternate arm converter; hvdc; hybrid multilevel converter; modular multilevel converter